REFLEKSI DIRI ISLAMI DALAM JOURNALING: UPAYA PROMOSI KESEHATAN MENTAL DI KALANGAN REMAJA - Maheswari Ayu Pratiwi; Khorun Nisa'; Ghina Ibra Syakira; Naia Elok Az Zahra; Amirul Haq Al Amin; Sultan Apriliano Lautan; Imtihanatul Ma’isyatuts Tsalitsah; Dewi Ilma Antawati (Archetype : Jurnal Ilmiah Psikologi dan Terapan, 2025)
Adolescent mental health is a growing concern in modern educational settings, particularly due to limited access to professional counseling and the persistent stigma surrounding psychological distress. This study explores the effectiveness of Islamic journaling as a spiritually grounded self-healing method implemented among high school students at SMA Muhammadiyah 7 Surabaya. The program was conducted using an educational and participatory approach, incorporating Islamic counseling concepts, journaling practices, and emotional reflection. A Project-Based Learning (PjBL) framework was used, accompanied by pre- and post-test assessments to evaluate cognitive, affective, and spiritual outcomes. The results indicate a significant improvement in students' understanding of Islamic counseling (from 33% to 90%), their ability to manage emotions in accordance with Islamic values (from 27% to 87%), and their comfort in expressing feelings through writing (from 30% to 90%). Furthermore, 93% of participants reported feeling more emotionally relieved after writing, and 90% expressed a desire to continue journaling independently. These findings suggest that Islamic journaling is a simple yet effective strategy for enhancing emotional regulation and spiritual awareness among adolescents. The program also demonstrates potential as a faith-based psychosocial intervention model for school settings. Keywords: Islamic journaling, adolescent mental health, emotional regulation, Islamic spirituality, self-healing